Towards information-rich bioprocessing: Generation of spatio-temporal profiles through the use of design of experiments to determine optimal number and location of sensors-An example in thermal profiles - Lim, M; Ye, H; Drakakis, E; Yue, X; Cass, A; Panoskaltsis, N; Mantalaris, A (2008)
Stem cell and tissue bioprocessing for regenerative medicine require robust, reproducible, controllable, and optimal processes. In vivo, the body utilises real-time, on-line, in situ monitoring to deliver this level of control. Increasingly, monitoring is becoming more applicable and extremely important in tissue engineering and regenerative medicine due to the advances in monitoring techniques, including the use of biosensors. However, determination of optimal sensor location and number remains to be explored. Herein, we have presented the novel application of design of experiments methodology to address this issue. A culture chamber (equivalent to a 6-well plate) was fabricated and temperature sensors were employed in studying the temperature profile of the chamber under both static and perfused (0.01 mL/min) conditions. Heating elements were used to provide a constant heat source in order to simulate the production of metabolites by the cells. The design of experiments determined the use of nine sensors at both factorial and axial locations. In comparison, two random designs utilising five and seven sensors confirmed that the design of experiments-generated data were information-rich and produced the spatial (and temporal) temperature profiles for the chamber. The implementation of this powerful technique would offer knowledge of the local concentration gradients of important culture parameters allowing for the real-time, local, 'intelligent' bioprocess control. © 2008.